9‐2: Invited Paper: Stretchable Electronics for Wearable Microvolt Biosignal Monitoring Systems. Issue 1 (30th May 2018) - Sekitani, Tsuyoshi; Yoshimoto, Shusuke; Araki, Teppei; Noda, Yuki; Uemura, Takafumi
Abstract : We report on recent progress in large, ultraflexible, and stretchable electronic sensors. Our work focuses on integration technologies for thin‐film electronics comprising ultrasoft gel electrodes, thin‐film amplifiers, Si‐LSI platforms, thin‐film batteries, and information engineering; integrating these technologies enables them to function as imperceptible active sensors. Here, we demonstrate the application of imperceptible sensors for a biosignal monitoring sheet system whose measurement accuracy is 0.1 µV. The most important technology for monitoring very small signals is flexible organic amplification circuits. Taking full advantage of flexible and stretchable electronic technology, we demonstrate wireless sheet electroencephalogram (EEG) monitoring systems for next‐generation telemedicine. The ultraflexible and compliant thin‐film amplifier can amplify biological signals by a factor of 3000, for monitoring of microvolt EEG signals.